The effect of altering head length on corrosion using a material loss method. Issue 4 (July 2019) - Lanting, Brent A; Wood, Thomas J; Young, Sam; Van Citters, Douglas W; MacDonald, Steven J; Howard, James L; Teeter, Matthew G
Introduction: Corrosion at head neck taper junctions in total hip arthroplasty has increasingly been reported in the literature. Debate persists as to the exact causes and clinical significance of corrosion. Increased offset and head length has been correlated with an increased risk of tribocorrosion due to an adverse mechanical environment. The purpose of this study is to assess the effect of head length on corrosion of a metal-on-polyethylene articulation. Methods: Retrievals from a single institution of 28-mm cobalt chromium alloy heads with a 12/14 taper from a single manufacturer were studied. Corrosion of femoral head bores were studied utilising a material loss method. Testing was performed using co-ordinate measuring for maximum linear wear depth. Results: 56 heads were examined with lengths of either −3, 0, +4 or +8 mm and all had been in situ for a minimum of 2 years. There were no significant differences in mean maximum linear wear depth (MLWD) ( p = 0.6545). There was no correlation found between MLWD and the time implants were in situ (Spearman coefficient −0.1157) and no significant difference seen between high or standard offset stems ( p = 0.1336). Conclusion: In contrast to studies using qualitative methodologies, there was no correlation between head length and material loss when confined to a 28-mm head. Broad application of this outcome should be cautioned against as this study examined 1 taper construct and a metal-on-polyethylene articulation.